Promoting postoperative recovery in older adult surgical patients: a randomized controlled trial of MDT-based perioperative comprehensive nutritional management model - An, Qi; Li, Yonghao; Shi, Jinxin; Liu, Chengyu; Li, Zijian; Chen, Liru; Gao, Linlin; Li, Lei; Liu, Qingmei; Cui, Hongyuan; Xi, Huan; Zhu, Mingwei (Frontiers in Nutrition, 2026)
BackgroundTraditional perioperative care is hospital-centric, whereas the efficacy of multidisciplinary team (MDT)-based comprehensive nutrition management remains debated. This study examines how this model impacts postoperative complications and functional recovery in older adults.MethodsA single-center superiority randomized controlled trial (RCT; April 2023–March 2024) randomized 120 older adults (≥65y) undergoing major abdominal surgery (grades 3–4) into intervention (n = 60) and control (n = 60) groups, excluding those with severe organ dysfunction or poor compliance. The MDT-based model included personalized exercise, nutrition, psychological support (3 weekly sessions, smoking/alcohol cessation), and post-discharge monitoring via wearables/WeChat. Control group received standard care.ResultsAmong 120 participants (mean age 72.6 years; 65.2% male), 5 were lost to follow-up, leaving 56 in the intervention group and 59 in the control group for analysis. The intervention group demonstrated significantly lower postoperative complications compared to controls, with a relative reduction in in-hospital events and lower post-discharge rates (3.6% vs. 6.8%). The Comprehensive Complication Index averaged 6.2 points lower in the intervention group (p = 0.175). Body composition improved significantly, showing reduced weight loss, reduced BMI loss, and increased appendicular skeletal muscle mass index. Postoperative hospital stay was shortened by a median of 3.67 days in the intervention group, which also reported higher rates of mobility improvement and pain relief (all p < 0.05).ConclusionThe MDT-based perioperative model synergistically reduces postoperative complications and accelerates geriatric functional recovery through nutritional, exercise, and psychological interventions, providing evidence-based support for high-risk elderly care.